Waste composting for urban and peri-urban agriculture: closing the rural-urban nutrient cycle in Sub-Saharan Africa - Drechsel, P.; Drechsel, P.; Kunze, D.; Kunze, D. (Wallingford :CABI Publishing, 2001)
Rapid urbanization has created a major challenge with regard to waste management and environmental protection. However, the problem can be ameliorated by turning organic waste into compost for use as an agricultural fertilizer in urban and peri-urban areas. This is especially significant in less developed countries, where food security is also a key issue. This book addresses these subjects and is mainly based on papers presented at a workshop held in Ghana by the International Board for Soil Research and Management (now part of the International Water Management Institute) and FAO. Special reference is given to sub-Saharan Africa, with acknowledgement to experiences from other parts of the world.
Keywords: JJ600 - Soil Fertility; JJ700 - Fertilizers and other Amendments; UU485 - Social Psychology and Social Anthropology, (New March 2000); XX300 - Human Wastes and Refuse; West Africa